1998
DOI: 10.2105/ajph.88.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric care and payment source: do low-risk Medicaid women get less care?

Abstract: OBJECTIVES: This study examined whether Medicaid-insured women at low risk receive less adequate obstetrical care than privately insured women. METHODS: Low-risk women who were cared for by a random sample of obstetrical providers in Washington State were randomly selected. Information on all prenatal and intrapartum services was abstracted from medical records. Service information was aggregated into standardized resource-use units. Results compared Medicaid-insured women with those who were privately insured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
9
0
2
Order By: Relevance
“…In another analysis using these data, there were few differences in the number of prenatal and intrapartum resources used by Medicaid and privately insured women. 26 Nonetheless, the current findings are consistent with a growing body of work showing that Medicaid patients or patients with demographic characteristics associated with Medicaid insurance status, such as being a racial or ethnic minority, are less likely to receive some medical advice, diagnostic tests, and therapeutic interventions than are their privately insured, white counterpartsP-3I This study is limited by several factors. First, our results are based on chart review.…”
Section: Discussionsupporting
confidence: 83%
“…In another analysis using these data, there were few differences in the number of prenatal and intrapartum resources used by Medicaid and privately insured women. 26 Nonetheless, the current findings are consistent with a growing body of work showing that Medicaid patients or patients with demographic characteristics associated with Medicaid insurance status, such as being a racial or ethnic minority, are less likely to receive some medical advice, diagnostic tests, and therapeutic interventions than are their privately insured, white counterpartsP-3I This study is limited by several factors. First, our results are based on chart review.…”
Section: Discussionsupporting
confidence: 83%
“…The two groups showed no significant differences in low birth weight or preterm birth rates. 19 Howell et al 20 compared obstetrical care and birth outcomes among four groups of women in California: short-term Medicaid enrollees (enrolled for 0-3 months of pregnancy), longterm Medicaid enrollees (enrolled for 4 or more months of pregnancy), non-Medicaid mothers living in low-income areas, and non-Medicaid mothers residing in high-income areas. Their findings revealed that Medicaid and non-Medicaid mothers residing in low-income areas had increased likelihood of receiving late prenatal care compared with mothers living in high-income areas.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] In addition, studies have shown that social status impacts on prenatal behavior and birth outcomes. [15][16][17][18] We speculated that the adverse outcomes of NEC and sepsis are secondary to multiple factors and not just the fact that they have MMC. NEC and BS data suggest that there may be some alteration in neonatal immune status in the MMC population.…”
Section: Discussionmentioning
confidence: 99%